2022
DOI: 10.1186/s12889-022-13662-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in short-acting reversible, long-acting reversible and permanent contraception use among currently married women in India

Abstract: Background In India, the usage of modern contraception methods among women is relatively lower in comparison to other developed economies. Even within India, there is a state-wise variation in family planning use that leads to unintended pregnancies. Significantly less evidence is available regarding the determinants of modern contraception use and the level of inequalities associated with this. Therefore, the present study has examined the level of inequalities in modern contraception use amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For instance, a multi-country study on household wealth and contraception use reported that poorer women in Bangladesh and India had higher inclination towards long-acting contraception methods, than the wealthier women [ 26 ]. This notwithstanding, other scholars have reported inconsistent findings, possibly due to variation in study design or differences in the socio-demographic characteristics of the samples studied [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, a multi-country study on household wealth and contraception use reported that poorer women in Bangladesh and India had higher inclination towards long-acting contraception methods, than the wealthier women [ 26 ]. This notwithstanding, other scholars have reported inconsistent findings, possibly due to variation in study design or differences in the socio-demographic characteristics of the samples studied [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…Evidence suggest that motivation for using long-acting methods include long term protection against unintended pregnancies, effectiveness and better child-spacing [ 12 , 33 ]. Though short-acting methods have competitive advantages, this finding might suggest that as women advance in age, they weigh long-acting methods to be more protective, safe, and reliable as compared with short term contraceptive methods [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…DHS asked about the type of contraceptive women aged 15–49 use, and those who were using an intrauterine device (IUD), implant and tubal litigation were categorised as using LARC/PMs, and other types of contraceptive use were categorised as not using LARC/PMs. The use of LARC/PMs or not was restricted to sexually active women who desire no more children in high fertility countries in SSA, as it has been measured in similar studies [ 7 , 21 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 25 ] Also, most researchers agree that rural women have limited access to and utilization of reproductive health services, including contraceptives. [ 32 , 40 ] National data from Yemen indicates that more than half of women of reproductive age rely on the public sector for contraceptive needs. [ 11 ] Unfortunately, the country’s protracted conflict has deteriorated the already fragile health system, resulting in severe gaps in the availability and access to vital health treatments, including family planning, among urban and rural women.…”
Section: Discussionmentioning
confidence: 99%